Implications of partial culling on African swine fever control effectiveness in Vietnam - Nga, Bui Thi To; Padungtod, Pawin; Depner, Klaus; Chuong, Vo Dinh; Duy, Do Tien; Anh, Nguyen Duc; Dietze, Klaas (Frontiers in Veterinary Science, 2022)
The introduction of African swine fever (ASF) into previously unaffected countries often overwhelms veterinary authorities with the resource demanding control efforts that need to be undertaken. The approach of implementing total stamping out of affected herds is taken as “default” control measure in many countries, regardless of the transboundary animal disease addressed, leading to a variety of challenges when implemented. Apart from organizational challenges and high demand of human and financial resources, the total stamping out approach puts a high burden on the livelihoods of affected farmers. After the spread of ASF throughout the country in 2019, Vietnam changed the culling approach enabling partial culling of only affected animals in the herd, in order to save resources, reduce the environmental impact due to carcass disposal and allow farmers to protect valuable assets. Until now, field data comparing these disease control options in their performance during implementation has not been evaluated scientifically. Analyzing the effect of the change in control policy, the present study concludes that partial culling can in average save over 50% of total stock with an 8-day prolongation of the implementation of control measures. With 58% of farms undergoing partial culling scoring high on a time-livelihoods matrix, whilst total stamping out fails to score on livelihoods, much needed clarity on the livelihood-protecting effects of alternative culling strategies is given. In the future, this will allow veterinary authorities to adjust control measures according to differing priorities, targeting peculiarities of ASF and acknowledging resource constraints faced.